Integrated knowledge of physics and chemistry: Physical Chemistry course - Gojak, Sabina; Galijašević, Semira; Hadžibegović, Zalkida; Zejnilagić-Hajrić, Meliha; Nuić, Ines; Korać, Fehim (Bulletin of Chemists and Technologists of Bosnia and Herzegovina, 2012)
One of the major achievements of the learning process is acquisition of integrated knowledge. This paper presents the first results of the degree of knowledge of the second year chemistry students in subjects relevant to the objects of physical chemistry. Data was collected using questionnaires and tests given out to students of chemistry in the academic year 2010/2011. The first results obtained show a weak and insufficient integration of knowledge in general chemistry, general physics and mathematics required for further subject courses such as physical chemistry. The negative difference in the number of points on the pretest and posttest (the results are lower for 80% of questions on the posttest) was detected, although the test was repeated after the end of the winter semester and completion of Physical chemistry course. This poor performance on tests can be an indicator of a number of difficulties in the learning process, which are identified through this research in attempt to find correct solution for this problem.